2014
DOI: 10.1016/j.ijheh.2013.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among 24,865 workers exposed to polychlorinated biphenyls (PCBs) in three electrical capacitor manufacturing plants: A ten-year update

Abstract: The objective of this analysis was to evaluate mortality among a cohort of 24,865 capacitormanufacturing workers exposed to polychlorinated biphenyls (PCBs) at plants in Indiana, Massachusetts, and New York and followed for mortality through 2008. Cumulative PCB exposure was estimated using plant-specific job-exposure matrices. External comparisons to US and state-specific populations used standardized mortality ratios, adjusted for gender, race, age and calendar year. Among long-term workers employed 3 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 47 publications
(45 reference statements)
0
48
1
1
Order By: Relevance
“…Numerous studies encompassing thousands of women have failed to detect an association between PCB levels in serum and breast cancer risk (Gammon et al, 2002;Rubin et al, 2006;Ruder et al, 2014). In this study, we observed the highest levels of PCB congeners in breast tissue from Groups II and III, which have been associated with breast cancer potential in vitro, but we detected no associations between total PCB levels, functional groupings, or individual congeners and clinical and pathological characteristics in women with breast disease.…”
Section: Discussioncontrasting
confidence: 60%
“…Numerous studies encompassing thousands of women have failed to detect an association between PCB levels in serum and breast cancer risk (Gammon et al, 2002;Rubin et al, 2006;Ruder et al, 2014). In this study, we observed the highest levels of PCB congeners in breast tissue from Groups II and III, which have been associated with breast cancer potential in vitro, but we detected no associations between total PCB levels, functional groupings, or individual congeners and clinical and pathological characteristics in women with breast disease.…”
Section: Discussioncontrasting
confidence: 60%
“…Relatively few studies have been conducted to look for specific environmental risk factors for melanoma, but among these, a number of studies have shown an elevated risk in individuals with suspected exposure to organochlorine compounds, such as polychlorinated biphenyls (PCBs) and some chlorine-based pesticides [1,146,161,198,203,207,208,220,240,248]. As noted above, although these studies have some significant limitations, the results, with few exceptions, for implied industrial PCB exposure have been fairly consistently positive.…”
Section: Pcbsmentioning
confidence: 99%
“…Despite the prohibition of OCPs in domestic and overseas, they were still extensively found in different regions owing to the historical residues themselves (Bozlaker et al 2009;Baek et al 2013). PCBs and OCPs could play important roles in some diseases on genital, nervous, endocrine, and respiratory system, leading to chronic-toxic effects and cancers (Ruder et al 2013). Both of these chemicals were classified as priority pollutants by the Environmental Protection Administration (EPA) on account of their high toxicity, carcinogenic property, and resistance to degradation (Bräuner et al 2011).…”
Section: Responsible Editor: Constantini Samaramentioning
confidence: 99%